Sealing Ability of AH Plus and GuttaFlow Bioseal. (22nd September 2020) - Lee, Soo-Hyuk; Oh, Soram; Al-Ghamdi, Adel Saeed; Mandorah, Ayman Omar; Kum, Kee-Yeon; Chang, Seok Woo
Abstract : The objective of root canal obturation is to achieve a fluid-tight seal. Recently, GuttaFlow bioseal (GB), a root canal sealer composed of polydimethylsiloxane, gutta-percha particles, and bioactive glass ceramics, has been developed, to enhance the sealing ability of root canal filling material. The objective of this study was to assess the sealing ability of GB using a subnanoliter-scaled fluid-flow measuring device and to compare with that of AH Plus (AH). The fluid flow in root canal-filled teeth using either gutta-percha cone (GP) with AH (GAR; n = 10) or GP with GB (GBR; n = 10) and in GP inserted in AH blocks (GA; n = 10) or GP inserted in GB blocks (GB; n = 10) was measured. In addition, fluid flow in sealer blocks of AH (A; n = 10) and GB (B; n = 10), which served as negative controls, was measured. Root canal-filled teeth using GP without any sealer (GR) acted as positive controls ( n = 10). The leakage was obtained by calculating the volume of moved water by time (s), after stabilization of the fluid flow was achieved. Statistical analysis was performed using the Kruskal–Wallis test and Mann–Whitney U -test with Bonferroni correction. A p value less than 0.00238 (0.05/21) was considered significantly different. The mean leakages (nL/s) in the groups are as follows: GAR, 0.0958 ± 0.0543; GBR, 0.0223 ± 0.0246; GA, 0.0644 ± 0.0803; GB, 0.0267 ± 0.0182; A, 0.0055 ± 0.0057; B, 0.0052 ± 0.005; and GR, 0.2892 ± 0.3018. The mean leakage in the GBR group was lower than that in the GAR group (p = 0.001), while the mean leakages in the GA and GB groups were not significantly different. GuttaFlow bioseal can be useful in single-cone obturation technique.